2022
DOI: 10.1155/2022/1140176
|View full text |Cite
|
Sign up to set email alerts
|

Structural Configuration of Blood Cell Membranes Determines Their Nonlinear Deformation Properties

Abstract: The ability of neutrophils and red blood cells (RBCs) to undergo significant deformations is a key to their normal functioning. Disruptions of these processes can lead to pathologies. This work studied the influence of structural configuration rearrangements of membranes after exposure to external factors on the ability of native membranes of neutrophils and RBCs to undergo deep deformation. The rearrangement of the structural configuration of neutrophil and RBC membranes under the influence of cytological fix… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 58 publications
0
4
0
Order By: Relevance
“…Following the authors of ref. 10,18 , the coefficient of elasticity of the cell membrane was significantly higher than the coefficient of elasticity of the cantilever beam. Differences are also visible in the near-surface area of action of adhesive forces.…”
Section: Resultsmentioning
confidence: 84%
See 3 more Smart Citations
“…Following the authors of ref. 10,18 , the coefficient of elasticity of the cell membrane was significantly higher than the coefficient of elasticity of the cantilever beam. Differences are also visible in the near-surface area of action of adhesive forces.…”
Section: Resultsmentioning
confidence: 84%
“…All this points to the complex mechanical organization of the cell membrane, which manifests itself only with its active stimulation with large force effect. In this regard, the authors of 10 showed that the mechanical action on the membranes of human erythrocytes and neutrophils with a force of up to 125 nN is accompanied by nonlinear effects of elastic deformation–a significant increase in the values of the Hooke’s coefficient K and Young’s modulus E with a decrease in the zone of uniform bending of the membrane. It should be noted that the authors of 10 divided the process of elastic deformation of membranes into three stages characterized by three deformation zones.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations